RISK FACTORS FOR DEVELOPING CHILDREN AND YOUNG PEOPLE DEPENDENT ON SUBSTANCE USE BEHAVIOR - Liakh, Tetiana; Spirina, Tetiana; Popova, Alona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
A pivotal feature of the vulnerability of families, in which there are persons who use psychoactive substances, is that such persons develop dependent behavior. It leads to serious violations of physical and mental health, loss of social contacts, etc. The roots of the addictive mechanisms of any addition should be sought in the childhood, in the peculiarities of upbringing, in the behavior of parents or one of them. The purpose of this article is to determine and substantiate the risk factors for the formation of addictive behavior in children and young people from the use of psychoactive substances. The results of the expert survey authors have joined a group of risk factors for developing children and young dependent behavior of the use of a couple of groups of "biological factors", "psychological factors", "family", "impact of peers", "impact of educational institution", "social influence" as well as proposed protective mechanisms for each of the groups. The study brings results of our own research in this area. A well-founded theory served as the basis for collecting data both at the theoretical level and at the level of processing the results of expert interviews. Determined by expert interviews risk factors for developing children and young people dependent on substance use behavior made it possible to develop a model needs assessment and decision on the future of social work with people who use psychoactive substances and their families.